PREVALENCE OF H. PYLORI INFECTION IN PATIENTS PRESENTING WITH PERFORATED DUODENAL ULCER - NAEEM , M; AHMAD , S; ULLAH , H; MUJAHID, .; ASLAM , AK; ALI , L; MASOOD , A (Biological and Clinical Sciences Research Journal, 2023)
A cross-sectional study was conducted at the Department of Gastroenterology Qazi Hussein Ahmad Medical Complex, Nowshera, from January 2020 to January 2022 to determine the prevalence of H-pylori infection in patients with a perforated duodenal ulcer. A total of 189 patients were enrolled in the study. The data was analyzed using SPSS version 19 statistical software. Categorical data was computed as frequency and percentages and mean ± SD was used for all numerical variables. Out of the 189 patients, 115 (60.85%) were male and had an average age of 43.70 ± 7.38, and 74 (39.15%) were female and had an average age of 45.72 ± 8.85. The study revealed that 98 (51.85%) patients tested positive for H. Pylori stool antigen, while 91 (48.15%) tested negative. Based on the findings, patients with a perforated duodenal ulcer are more likely to have an infection with Helicobacter pylori. Therefore, it is crucial to conduct a thorough examination of such cases. Early diagnosis and treatment of H-pylori infection can prevent harmful consequences for the patient.